Valproic acid confers functional pluripotency to human amniotic fluid stem cells in a transgene-free approach - Moschidou, D.; Mukherjee, S.; Blundell, M.P.; Drews, K.; Jones, G.N.; Abdulrazzak, H.; Nowakowska, B.; Phoolchund, A.; Lay, K.; Ramasamy, T.S.; Cananzi, M.; Nettersheim, D.; et al. (2012)
Induced pluripotent stem cells (iPSCs) with potential for therapeutic applications can be derived from somatic cells via ectopic expression of a set of limited and defined transcription factors. However, due to risks of random integration of the reprogramming transgenes into the host genome, the low efficiency of the process, and the potential risk of virally induced tumorigenicity, alternative methods have been developed to generate pluripotent cells using nonintegrating systems, albeit with limited success. Here, we show that c-KIT+ human first-trimester amniotic fluid stem cells (AFSCs) can be fully reprogrammed to pluripotency without ectopic factors, by culture on Matrigel in human embryonic stem cell (hESC) medium supplemented with the histone deacetylase inhibitor (HDACi) valproic acid (VPA). The cells share 82 transcriptome identity with hESCs and are capable of forming embryoid bodies (EBs) in vitro and teratomas in vivo. After long-term expansion, they maintain genetic stability, protein level expression of key pluripotency factors, high cell-division kinetics, telomerase activity, repression of X-inactivation, and capacity to differentiate into lineages of the three germ layers, such as definitive endoderm, hepatocytes, bone, fat, cartilage, neurons, and oligodendrocytes. We conclude that AFSC can be utilized for cell banking of patient-specific pluripotent cells for potential applications in allogeneic cellular replacement therapies, pharmaceutical screening, and disease modeling.